Tracheal Intubation through the I-gel for Emergency Cesarean Section in a Patient with Multidrug Hypersensitivity: A New Technique. (20th July 2014) - Samala, Kartika Balaji; Uchiyama, Yuri; Tokinaga, Yasuyuki; Niiyama, Yukitoshi; Iwasaki, Soshi; Yamakage, Michiaki
Abstract : 31-year-old female with hypersensitivity to local anesthetics and neuromuscular blocking agents presented for emergency Cesarean section. We successfully performed I-gel-assisted tracheal intubation without using neuromuscular blockers. We believe this method would be helpful in selected situations.